Association between periodontitis and risk of Alzheimer′s disease, mild cognitive impairment and subjective cognitive decline: A case–control study. (9th November 2018) - Holmer, Jacob; Eriksdotter, Maria; Schultzberg, Marianne; Pussinen, Pirkko J.; Buhlin, Kåre
Abstract: Aims: To test the hypothesis that periodontal disease contributes to increased risk of mild cognitive impairment (MCI), subjective cognitive decline (SCD) and Alzheimer′s disease (AD). Materials and methods: This case–control study was conducted over a 3‐year period in the municipality of Huddinge, Sweden. In total, 154 cases were consecutively enrolled from the Karolinska Memory Clinic at the Karolinska University Hospital and allotted to three diagnostic groups: AD, MCI and SCD, collectively referred to as "cases." Seventy‐six cognitively healthy age‐ and gender‐matched controls were randomly sampled through the Swedish population register. All cases and controls underwent clinical and radiographic oral examinations. Statistical analysis was based on logistic regression models adjusted for potential confounders. Results: Poor oral health and marginal alveolar bone loss were more prevalent among cases than among controls. The cases group was associated with generalized marginal alveolar bone loss (odds ratio [OR] = 5.81; 95% confidence interval [CI] = 1.14–29.68), increased number of deep periodontal pockets (OR = 8.43; CI 4.00–17.76) and dental caries (OR = 3.36; CI 1.20–9.43). Conclusion: The results suggest that marginal periodontitis is associated with early cognitive impairment and AD. However, the study design does not preclude noncausal explanations.